Glioblastomas exploit truncated O-linked glycans for local and distant immune modulation via the macrophage galactose-type lectin - Dusoswa, Sophie A. (2020)
Glioblastoma is the most aggressive brain malignancy, for which immunotherapy has failed to prolong survival. Glioblastoma-associated immune infiltrates are dominated by tumor-associated macrophages and microglia (TAMs), which are key mediators of immune suppression and resistance to immunotherapy. We and others demonstrated aberrant expression of glycans in different cancer types. These tumor-associated glycans trigger inhibitory signaling in TAMs through glycan-binding receptors. We investigated the glioblastoma glycocalyx as a tumor-intrinsic immune suppressor. We detected increased expression of both tumor-associated truncated O-linked glycans and their receptor, macrophage galactose-type lectin (MGL), on CD163+ TAMs in glioblastoma patient-derived tumor tissues. In an immunocompetent orthotopic glioma mouse model overexpressing truncated O-linked glycans (MGL ligands), high-dimensional mass cytometry revealed a wide heterogeneity of infiltrating myeloid cells with increased infiltration of PD-L1+ TAMs as well as distant alterations in the bone marrow (BM). Our results demonstrate that glioblastomas exploit cell surface O-linked glycans for local and distant immune modulation.